Bibliometric analysis of scientific production on research national agenda in Peru 2011-2014 - Romani Romani, Franco Ronald (2016)
Objectives. To analyze the scientific production framed in the National Research Agenda 2011-2014. Design. Bibliometric research using SCOPUS, LILACS and LIPECS databases. Setting National Health Institute, Lima, Peru. Unit of analysis. Original article with at least one researcher with a Peruvian institution affiliation or whose study population or part of it, came from Peru and framed on any issue of national research agendas. Main outcome measures. Bibliometric indicators of production. Results. Out of the 882 publications retrieved, 215 (24.4%) were admitted to the analysis. The national research agendas with more scientific production were tuberculosis and STD-HIV/AIDS that included 78 and 59 articles respectively. The most common language of publication was English (69.8%). The articles were published in 90 scientific journals. Peruvian institutions with the highest number of signatures were the Universidad Peruana Cayetano Heredia (49.3%), followed by the Ministry of Health (19.5%) and the National Institute of Health (14.4%). The National Institutes of Health (USA) participated in the financing of 50.7% of the articles analyzed. Peruvian institutions that funded more research were the National Institute of Health (4.2%) and the Ministry of Health (2.8%). Conclusions. Peruvian scientific production framed in the six national research agendas in the period 2011-2014 is limited and focused on tuberculosis and STI-HIV / AIDS research; funding was primarily by international institutions.